Pharmaco-economic and market analysis of ATE-inhibitor in the treatment of hypertension in the hospital - O. P. Balitska (Zaporožskij Medicinskij Žurnal)
Cohort research based on 180 patients with hypertension treated in cardiological department was carried out in Vinnitsa regional hospital in 2011–2012. Pharmacoeconomic analysis of prevalent schemes of essential hypertension medication was done.